2019
DOI: 10.1002/cne.24640
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Zika virus infection in the ferret

Abstract: Although initial observations of infections with the Zika virus describe a mild illness, more recent reports show that infections by Zika result in neurotropism. In 2015, substantial congenital malformations were observed, with numerous infants born with microcephaly in Brazil. To study the underlying mechanism and effects of the disease, it is critical to find suitable animal models. Rodents lack an immune system parallel to humans and also have lissencephalic brains, which are likely to react differently to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…These findings are in line with reports showing that endothelial cells-a key component of developing vasculature in the fetal brain-also express the AXL receptor and are prime targets of infection (Richard et al 2017). Zika administration in gravid ferrets produced a similar increase in cortical vessel size in the embryonic ferret cortex (Hutchinson et al 2019), whereas studies in the mouse have reported a decrease in vascular density and vessel branching (Garcez et al 2018). These contrasting findings, particularly between embryonic mouse and fetal rhesus monkey, may represent species differences, contrasting patterns of vascular development between lissencephalic versus gyrencephalic cortices, and/or differences in methodology.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are in line with reports showing that endothelial cells-a key component of developing vasculature in the fetal brain-also express the AXL receptor and are prime targets of infection (Richard et al 2017). Zika administration in gravid ferrets produced a similar increase in cortical vessel size in the embryonic ferret cortex (Hutchinson et al 2019), whereas studies in the mouse have reported a decrease in vascular density and vessel branching (Garcez et al 2018). These contrasting findings, particularly between embryonic mouse and fetal rhesus monkey, may represent species differences, contrasting patterns of vascular development between lissencephalic versus gyrencephalic cortices, and/or differences in methodology.…”
Section: Discussionsupporting
confidence: 87%
“…Since ferrets exhibit an expanded and folded neocortex, they are suitable for modeling diseases such as microcephaly ( Johnson et al, 2018 ) and lissencephaly ( Shinmyo et al, 2017 ). Considering the important role of ferrets in virology and immunology for modeling human influenzas, it is important to emphasize the role of ferrets for studying the neurotropic effects of viruses such as Zika ( Hutchinson et al, 2019 ) and SARS-CoV-2. Combining the previous application in neurodevelopmental disorders and viral infections, the ferret is becoming an emerging model organism for studying the relationship between the maternal immune activation and neuropsychiatric diseases ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ferret has been used in research involving infection by Zika virus due to the similarity of both the immune responses and certain neurodevelopmental features with those of human, referred to earlier in this review ( Hutchinson et al, 2019 ). Zika virus is neurotropic and an infection during pregnancy in humans can lead to neurodevelopmental malformations, such as microcephaly, i.e.…”
Section: The Ferret As a Model For Human Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zika virus affects the brain during development and can result in severe neurologic impairments. The infection of Zika virus during pregnancy may cause fetal malformations . Aedes aegypti Linn, the principal vector of dengue virus, originated in Africa, but is now found throughout the world in tropical and subtropical regions .…”
Section: Introductionmentioning
confidence: 99%